2022
DOI: 10.1126/sciadv.ade0189
|View full text |Cite
|
Sign up to set email alerts
|

Main group catalysis for H 2 purification based on liquid organic hydrogen carriers

Abstract: Molecular hydrogen (H 2 ) is one of the most important energy carriers. In the midterm future, a huge amount of H 2 will be produced from a variety of hydrocarbon sources through conversion and removal of contaminants such as CO and CO 2 . However, bypassing these purification processes is desirable, given their energy consumption and environmental impact, which ultimately increases the cost of H 2 . Here, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Finally, we applied B 2 to the catalytic hydrogenation of Qin using a gaseous mixture of H2/CO/CO2 (1/1/1 molar ratio), a model of the crude H2 that is produced from a variety of carbonbased resources such as natural gas and biomass (Scheme 3B). 8,21 H4-Qin was obtained in >99% yield, demonstrating that Qin can be potentially used as an organic material that simultaneously separates and stores H2 directly from crude gaseous H2. This study proposes a strategy of modulating the 'remote' back strain of triarylboranes to finely tune their Lewis acidity by varying the size and shape of their aryl meta-substituents.…”
Section: Template For Synlett Thiemementioning
confidence: 98%
See 1 more Smart Citation
“…Finally, we applied B 2 to the catalytic hydrogenation of Qin using a gaseous mixture of H2/CO/CO2 (1/1/1 molar ratio), a model of the crude H2 that is produced from a variety of carbonbased resources such as natural gas and biomass (Scheme 3B). 8,21 H4-Qin was obtained in >99% yield, demonstrating that Qin can be potentially used as an organic material that simultaneously separates and stores H2 directly from crude gaseous H2. This study proposes a strategy of modulating the 'remote' back strain of triarylboranes to finely tune their Lewis acidity by varying the size and shape of their aryl meta-substituents.…”
Section: Template For Synlett Thiemementioning
confidence: 98%
“…We have recently investigated the hydrogenation of 2methylquinoline using a gaseous mixture of H2/CO/CO2 and Mahiro Sakuraba a Taichi Morishita a Taiki Hashimoto a Sensuke Ogoshi* a Yoichi Hoshimoto* a,b Synlett Letter / Cluster / New Tools Template for SYNLETT Thieme demonstrated that the catalyst turnover number (TON) increases significantly when the meta-substituent R in B(2,6-Cl2-C6H3)(2,6-F2-3,5-R2-C6H)2 was changed from F (TON 1000) to Cl (TON 1400) and finally to Br (TON 1520). 8 Given their nearly identical energy levels of the p orbitals on each boron center, we speculated that the size and shape of the meta-substituents (R in Figure 2) could have a substantial impact on the Lewis acidity and reactivity of BAr3 (or BAr2Ar′) via control of the 'remote' back strain. Herein, we report the synthesis of novel homoleptic boranes B(2,6-F2-3,5-R2-C6H)3 (B 1 : R = trimethylsilyl, TMS; B 2 : R = allyl) to evaluate the impact of the remote back strain on the global and effective Lewis acidity by comparison with B 3 (R = H) (Figure 2).…”
mentioning
confidence: 99%
“…Ogoshi, Hoshimoto and coworkers reported organoboranecatalyzed dehydrogenation applied to the purification of molecular hydrogen (Scheme 15). 30 Scheme 15 Borane-mediated hydride abstraction for the interconversion of liquid organic hydrogen carriers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1,2 Hydrogen, as a clean and renewable energy, is considered as a promising candidate for fossil fuels, thanks to its high energy density and zero CO 2 emissions. 3,4 Until now, there are various methods to produce hydrogen energy, including natural gas reformation, 5 coal gasification, 6 and water splitting. 7 Among these, water splitting using electrochemical technology is regarded as the greenest, most simple, and efficient approach to generate hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing consumption of fossil fuels and deterioration of environment have compelled researchers to explore sustainable, green, and environmentally friendly energy sources to replace fossil fuels. , Hydrogen, as a clean and renewable energy, is considered as a promising candidate for fossil fuels, thanks to its high energy density and zero CO 2 emissions. , Until now, there are various methods to produce hydrogen energy, including natural gas reformation, coal gasification, and water splitting . Among these, water splitting using electrochemical technology is regarded as the greenest, most simple, and efficient approach to generate hydrogen. Nowadays, Pt/C is regarded as a benchmark catalyst for hydrogen evolution reaction (HER), while IrO x /RuO x are the benchmarks of oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%